Reference interval for type III procollagen (PIIINP) using the Advia centaur PIIINP assay in adults and elderly - Pettersson-Pablo, Paul; Samyn, Dieter; Wasim, Jamil; Vink, Martin (Scandinavian journal of clinical and laboratory investigation, 2021)
The amino-terminal peptide of type III procollagen (PIIINP) is a byproduct of type III collagen synthesis that exhibits promise as a biomarker of fibrosis, specifically in monitoring hepatic fibrosis in methotrexate treated patients. The Advia Centaur ® PIIINP assay is developed for track-based automated laboratory systems and is suitable for large volume analysis. Reference intervals in children and younger adults have been published previously. Here we measured PIIINP to determine reference ranges, specifically including elderly patients, for whom such are currently lacking. Samples were collected from subjects ranging from 20 to 98 years of age. Blood donors and clinical samples from primary care patients were used for reference interval calculation. Samples were analysed using the Advia Centaur ® PIIINP assay. After exclusion of samples high in alanine transaminase (AST), aspartate transaminase (ALT), and C-reactive protein (CRP) 386 samples were used in the reference interval calculation. We determined the following reference interval for the Advia Centaur ® PIIINP assay: the lower limit of the reference interval (2.5% percentile with 95% CI) was 4.42 (4.20-4.65) µg/L and the upper limit of the reference interval (97.5% percentile 95% CI) 16.0 (15.04-17.02) µg/L.No significant differences in mean PIIINP concentrations were found between men and women. While differing mean PIIINP concentrations were seen among subjects in different age groups, the differences were small and partitioning of reference range was determined not to be necessary.